Methods For Studying Honckenya peploides Genetics - Sigurður Halldór Árnason 1980- (2012)
The objective of this study was to test di erent methods for studying Honckenya peploides genetics. ISSR-PCR analysis was carried out on 11 individuals the Sea Sandwort, Honckenya peploides collected from populations in the Vestmannaeyjar archipelago. A total of 23 ISSR markers were generated from all 11 samples with one primer (AG)8, containing a 3' anchor (T), designed to anneal to dinucleotide repeats. ISSR along with clustering methods and statistical analysis revealed the presence of a Hermaphrodite determining marker, 500Bp in length, as well as a signi cant correlation between latitude and frequency of hermaphrodism within the population. Cytological work was also conducted on 3 individuals of H. peploides, resulting in a karyotype con rming prior chromosome number counts for Icelandic populations as well as the discovery of 2 possible satellites on one pair of chromosomes. A total of 386 individuals were also collected from populations of H. peploides located in Surtsey, Vestmannaeyjar, mainland Iceland, Greenland and Denmark. DNA was isolated using the CTAB method, slightly modi ed for AFLP and preliminary analysis was then carried out on 16 of these individuals using the AFLP method with two primer combinations. The results of this study indicate that (1) The ISSR method can be used to identify DNA fragments that can be linked to plant characteristics, (2) the cytogenetic methods employed here can be used to study polyploidy in this species and (3) the AFLP method will be suitable for studying population genetics of H. peploides with a large sample size from a wide geographic area.